PENINGKATAN KOMPETENSI GURU DALAM MENYUSUNRENCANA PROGRAM PEMBELAJARAN HARIAN (RPPH)MELALUI PERAN PENGAWAS SEKOLAH DI TK PERTIWI MEDAN - Ramsa Lumban Gaol (JURNAL TEMATIK, 2019)
This study aims to improve the competence of teachers in compiling the DailyLearning Implementation Plan through the role of the school supervisor. This type ofresearch is school action research. The object of this study was to improve teachercompetency in preparing RPPH through the role of school supervisors. Subjects were 7teachers at TK Pertiwi. The research process was carried out through 2 cycles. Datacollection uses observation sheets, interviews, and questionnaires. Guidance and trainingprovided by school supervisors can improve teacher competence in preparing RPPH. Itcan be proven from the results of observations that show that there is an increase inteacher competence in preparing RPPH from cycle to cycle, which is equal to 26.26.Based on the results of this study, it was found that the role of school supervisors couldimprove the competence of teachers in preparing RPPH at TK Pertiwi Medan.